2007
DOI: 10.1007/s10600-007-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification, and enzymatic activity of cellulase components of the fungus Aspergillus terreus

Abstract: The accumulation dynamics of cellulolytic enzymes in culture media of the basidiomycete fungi Panus tigrinus, Pleurotus ostreatus, Fomes fomentarus, and the micromycete Aspergillus terreus were studied during a long incubation period. It was found that A. terreus was the most active producer of cellulolytic enzymes among the studied fungi. Two protein fractions with cellulase activity were isolated using gel filtration and ion-exchange chromatography. PAAG electrophoresis showed that fraction-I consisted of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…In the case of cellulase, to our knowledge, there are no such studies to recover the enzyme, apart from conventional salt precipitation techniques and ion-exchange or gel permeation chromatography using state-of-the-art polymeric resins (Avelino et al 1999;Roy et al 1999;Amritkar et al 2004;Mirzaakhmedov et al 2007;Wang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of cellulase, to our knowledge, there are no such studies to recover the enzyme, apart from conventional salt precipitation techniques and ion-exchange or gel permeation chromatography using state-of-the-art polymeric resins (Avelino et al 1999;Roy et al 1999;Amritkar et al 2004;Mirzaakhmedov et al 2007;Wang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Even though these biopolymers have been widely reported individually for purification of bioproducts (Shi et al 2003;Hoven et al 2007;Torres et al 2007;Feng et al 2009;Xu et al 2009), very few records exist regarding their combined use for biomolecule adsorption. In the case of cellulase, to our knowledge, there are no such studies to recover the enzyme, apart from conventional salt precipitation techniques and ion-exchange or gel permeation chromatography using state-of-the-art polymeric resins (Avelino et al 1999;Roy et al 1999;Amritkar et al 2004;Mirzaakhmedov et al 2007;Wang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Fusarium are common in plants as endophytes and pathogens and have been described as producers of active cellulases [ 64 ]. Fusarium oxysporum and Aspergillus terreus were described with a slightly more effective cellulase with a specific activity of 0.9 U/mg [ 65 ], and 0.56–0.85 U/mg, respectively [ 66 , 67 ]. By checking the CAZy database only one putative cellulose (GH5) from Fusarium solani (more related to FW16.1) was found [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Penicillim species are inferior to three of the present isolates. According to Mirzaakhmedov et al (2007), A. terrus was the most active producer of cellulolytic enzymes than Penicillum, Fusarium, Trichoderma and other Aspergillus species. The present study also indicated that A. terrus was better than Penicillium species, though inferior to Isolate 'E' and Alternaria species.…”
Section: Discussionmentioning
confidence: 99%